Gestión de cobranza y cartera morosa en la empresa AMI – Servicio Médico Complementario, 2021 - Vela Alva, Sandra Analí (2022)
The present work titled "Collection management and nonperforming portfolio in the company AMI – Servicio Médico Complementario - 2021", aims to describe the experience acquired, the responsibilities in charge and the functions carried out during the year 2021, in the company AMI - Servicio Médico Complementario. Likewise, the increase in nonperforming in the domiciliary and debit portfolios was identified as the main problem, which were treated through various solutions, including letters to defaulters after 30 days, implementation of a coordination system with the commercial area and a system to identify those clients who made a change in their affiliated cards, in this way the nonperforming percentage were reduced. Information collected allowed a broader vision of the theoretical bases under which the collection management and nonperforming portfolio of a company works, especially those applied to AMI; as well as information also provided by the AMI company database and by the experience lived throughout the year 2021.